INVESTIGATION OF FORMS OF ENGINEERING CONTRACTS, CONCLUDED ON THE WORLD MARKET - A. Laznik (Вестник университета)
This article shows the results of analysis of the forms of engineering contracts presented on the world market. EPC and EPCM contracts are singled out as the most suitable for use in the construction of oil and gas facilities due to their specific features. In the article the analysis of the selected forms is carried out with the definition of key features and differences between them, as well as the modeling of the processes that arise when these contracts are executed.